Multiple Skin and Brain Abscess Caused by Salmonella Typhi, First Reported Case in Bangladesh - Siddiqui, Mahmudur Rahman; Islam, Quazi Tarikul; Rahman, Yousuf Ur; Shena, Tamanna Yasmin (Bangladesh Journal of Medicine, 2015)
Focal Brain and skin abscesses due to Salmonella are rarely reported. They tend to occur in patients who are immunosuppressed and in those with other predisposing factors like; sickle cell disease. We presented a case of a 28-year-old female of multiple skin and brain abscesses caused by Salmonella Typhi with no predisposing factor. After starting treatment according to culture and sensitivity report, she completely recovered without any residual disability. Bangladesh J Medicine Jul 2015; 26 (2) : 83-85